Neurotoxic effects of oxygen in hyperbaric environment: A case report - Rabrenović, Milorad S; Trešnjić, Saša; Rabrenović, Violeta; Čikiriz, Nikola; Mašić, Siniša; Matunović, Radomir (Vojnosanitetski pregled, 2015)
organisms. However, if not controlled, inhalation of oxygen under increased pressure in conditions of hyperbaric oxygen therapy can lead to serious damage and even death. Case report. We presented a 20-year-old male who had begun exhibiting symptoms of epilepsy during diving test in a hyperbaric chamber while inhaling 100% oxygen. He was immediately taken off oxygen mask and started breathing air and began rapid decompression. He lost consciousness, began foaming at the mouth, and had a series of tonic spasms. The patient was previously completely healthy and not on any medications. He was admitted for emergency treatment in our hospital, where he was treated for epilepsy. On admission, he complained of muscle and joint pain, and had erythematous changes on the forehead, neck and chest. All these changes occurred after leaving the hyperbaric chamber. Bloodwork revealed leukocytosis with neutrophil (Leukocytosis 16.0 ´ 109/L (reference values 4.00–11.00 ´ 109/L), Neutrophili 13 ´ 109/L (reference values 1.9–8.0 ´ 109/L), with elevated enzymes aspartate aminotransferase (AST) 56 U/L (reference values 0–37 U/L), alanin aminotransferase (ALT) 59 U /L, (reference values 25–65 U/L), creatine kinase (CK) 649 U/L, (reference values 32–300 U /L), lactate dehydrogenase (LDH) 398 U/L (reference values 85–227 U/L). Because of pain and his condition we began treatment in a hyperbaric chamber at a pressure of 2.0 ATA for 70 minutes, resulting in a reduction of symptoms and objective recovery of the patient. Within 24 h, repeated laboratory tests showed a reduction of leukocytosis (13 ´ 109/L and neutrophils (7.81 ´ 109/L), and the gradual reduction of the enzymes AST (47 U/L), ALT (50 U/L, CK (409 U/L), LDH (325 U/L). Since head CT and EEG were normal, epilepsy diagnosis was ruled out. This fact, along with medical tests, facilitated the differential diagnosis and confirmed that this was a case of neurotoxic effects of oxygen while the patient was in a hyperbaric chamber, not epileptic seizures. Conclusion. This case report suggests that in patients with symptoms of epileptic seizures while undergoing treatment in a hyperbaric chamber, it is always important to think of neurotoxic effects of pure oxygen which occurs at higher pressures and with a longer inhalation of 100% oxygen. In these patients, reexposure to hyperbaric conditions leads to recovery. This effect is important in daily inhalation of 100% oxygen under hyperbaric conditions which is why the use of pure oxygen is controlled and diving is allowed in shallow depths and for a limited time.